Power allocation based on Convex Optimization Theory for fading channels in OFDM-based cognitive radio networks - Tang Lun; Hu Lin; Wang Huan; Chen Qian-bin (2009 International Conference on Wireless Communications and Signal Processing, 2009)
A cognitive radio network (CRN) is formed by allowing the secondary user (SU) to opportunistically access the frequency bands originally allocated to primary user (PU) as long as its interference does not degrade the quality of service (QoS) of PU to an unacceptable level. Specially, by using a suboptimal scheme, we analyze the ergodic capacity under three types of constraints which satisfy primary QoS requirements for delay-insensitive, delay-sensitive and mixed applications, respectively. In particular, considering different fading channel models, we further provide the closed-form expressions for ergodic capacity of SU subject to corresponding constraints. Numerical simulation results corroborating our theoretical analysis were also provided.